Protective Effects of Hydrogen Sulfide on Testicular Injury Induced by Ischemia-Reperfusion in Wistar Rats - Z Nouri; S Yari; P Hasanein; A Hossein pour Malakouti (Armaghane Danesh Bimonthly Journal)
Background & aim: Testicular torsion is an emergency urological condition characterized by the twisting of the spermatic cord, leading to restricted blood flow to the testes and ultimately resulting in testicular atrophy. Ischemia-reperfusion (I/R) injury caused by testicular torsion induces apoptosis in germ cells and disrupts spermatogenesis, leading to testicular damage. Hydrogen sulfide (H₂S), due to its anti-inflammatory, antioxidant, and anti-apoptotic properties, provides protective effects and may serve as a potential therapeutic option to mitigate infertility disorders associated with testicular ischemia. As a result, the aim of the present study was to determine and investigate the protective effect of hydrogen sulfide on testicular injury induced by ischemia-reperfusion in Wistar rats.